2017
DOI: 10.31797/vetbio.336079
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological changes of rainbow trout after experimental infection with Lactococcus garvieae

Abstract: The purpose of this study is to determine both clinical and histopathological changes in experimentally infected rainbow trout with Lactococcus garvieae. Fourty healthy fish samples (50-60 g in weight) were purchased from a commercial farm near Antalya, Turkey and transferred to the laboratory. Each group of fish were challenged a cell density of 6x10 5 cfu/ml of L. garvieae isolate. The control group was given with the appropriate dilution of the sterile PBS. Fish showed darkening of skin color, lesion on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
2
1
0
Order By: Relevance
“…L. garvieae isolates recovered in this study showed a similar biochemical profile with the previous fish lactococcosis reports (Ringo and Gatesoupe, 1998;Vendrell et al, 2006) and this identification was confirmed with molecular identification (Zlotkin et al, 1998;Altun et al, 2013;Didinen et al, 2014;Korun et al, 2017;Balta and Balta, 2019). Use of improper antibiotic substance may be ineffective for disease treatment and hence causes economical losses.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…L. garvieae isolates recovered in this study showed a similar biochemical profile with the previous fish lactococcosis reports (Ringo and Gatesoupe, 1998;Vendrell et al, 2006) and this identification was confirmed with molecular identification (Zlotkin et al, 1998;Altun et al, 2013;Didinen et al, 2014;Korun et al, 2017;Balta and Balta, 2019). Use of improper antibiotic substance may be ineffective for disease treatment and hence causes economical losses.…”
Section: Discussionsupporting
confidence: 86%
“…Similar to the previous lactococcosis cases, fish samples showed various histopathological symptoms such as tubular degeneration, periglomerular edema and melanomacrophage centers in the kidney Timur et al, 2011;Avcı et al, 2014;Didinen et al, 2014;Ürkü and Timur 2014). But, liquefactive necrosis in the liver and kidney that were demonstrated previously (Timur et al, 2011;Ürkü and Timur, 2014;Korun et al, 2017) were in a more advanced stage than our samples.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation